Oxygen dynamics in eastern tropical South American estuaries: effects of human activities and climate variability - Ester M. Dos Santos; Mário Barletta; Francisco J. A. Cysneiros; Stephan Carty; Julia C. M. Pereira; Eloisa R. V. Reis; Anderson L. R. Paiva (Frontiers in Marine Science, 2026)
Dissolved oxygen (DO) dynamics in estuarine ecosystems are shaped by both anthropogenic activities and climate variability, which jointly influence oxygen concentrations and overall ecosystem health. This study examined temporal and spatial variations in DO across three coastal sectors in Eastern South America. DO levels were classified as hypoxia (<2.0mgL-¹),intermediate(2.0–4.0mgL¹), and optimum (>4.0mgL-¹).Hypoxia was associated with elevated BOD, ammonia, and phosphorus, particularly in the Metropolitan sector, where low DO persisted year-round. In this sector, hypoxia rates exceeded 40% during multiple years (2005–2008 and 2010–2013). The North (2005) and South sectors (2005 and 2007) also experienced hypoxia, mainly during dry periods, with DO levels below 2.0 mg L⁻¹ in specific years. Climate variability, especially El Niño–Southern Oscillation (ENSO) events, intensified hypoxia during droughts. In the Metropolitan sector, consecutive El Niño and La Niña years (2006 and 2008) resulted in a 40% hypoxia rate. The Northern sector exhibited 38% hypoxia during the 2005 El Niño event. Increased water movement under favourable oxygen conditions enhanced oxygenation. Salinity, temperature,pH, and spatial heterogeneity were also significant determinants. These findings indicate that oxygen dynamics are regulated by both persistent pollution and interannual climate variability. The results highlight the need for integrated management strategies that address anthropogenic impacts and the rising frequency of climate extremes.

Long-term water nutrient variations along the easternmost south American estuarine and coastal areas - Ester Milena dos Santos; Mário Barletta; Francisco José A. Cysneiros; Doris Veleda; Pedro Tyaquiçã Santos; Stephan Carty; Anderson Luiz Ribeiro de Paiva (Marine Pollution Bulletin, 2026)

Top predator feeding ecology and microplastic (MP) contamination on the far eastern South American coast: Evidence of MP trophic biotransfer - Roger R.R.C.B. Melo; Mário Barletta; Francisco F.J.A. Cysneiros; Maria Inês B. Tavares; Karoline da Silva Santana; Stephan Carty; Simon A. Morley (Estuarine, Coastal and Shelf Science, 2024)